2021
DOI: 10.1007/s40120-021-00310-y
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and Ischemic Stroke: A Mendelian Randomization Study

Abstract: Introduction: Previous epidemiological studies have found an increased risk for ischemic stroke in patients with migraine; however, the evidence for a causal relationship between migraine and ischemic stroke is scarce. This study aims to explore the potential causal relationship between migraine and ischemic stroke and its subtypes [including large artery stroke (LAS), small vessel stroke (SVS), and cardioembolic stroke (CES)]. Methods: We used data on genetic variants associated with migraine identified from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Third, we excluded SNPs associated with the outcome (DVT) ( P < 1 × 10 ––5 ). Fourth, the PhenoScanner database 2 was used to assess whether the selected SNPs were associated with confounders ( 41 ). We considered the risk factors and potential confounders of DVT (obesity, age, sex, smoking, physical activity, use of lipid-lowering therapy, Factor V Leiden, cancer, recent major surgery and study, and for women only the use of oral contraceptives, use of hormone-replacement therapy, and menopausal status) ( 42 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, we excluded SNPs associated with the outcome (DVT) ( P < 1 × 10 ––5 ). Fourth, the PhenoScanner database 2 was used to assess whether the selected SNPs were associated with confounders ( 41 ). We considered the risk factors and potential confounders of DVT (obesity, age, sex, smoking, physical activity, use of lipid-lowering therapy, Factor V Leiden, cancer, recent major surgery and study, and for women only the use of oral contraceptives, use of hormone-replacement therapy, and menopausal status) ( 42 ).…”
Section: Methodsmentioning
confidence: 99%
“…We used Cochran’s Q statistic for MR-IVW analyses and Rucker’s Q statistic for MR Egger analyses to detect heterogeneity, and P -value > 0.05 was considered to indicate no heterogeneity ( 43 ). We used the MR Egger method to assess the extent to which directional pleiotropy may affect risk estimates by intercept tests, and P -value > 0.05 was considered to indicate no horizontal pleiotropy ( 41 ). Because MR Egger may show lower accuracy in some cases, the MR pleiotropy residual sum and outlier (MR-PRESSO) method was also used to assess outlier SNPs and potential horizontal pleiotropy ( 41 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the many published MR studies that examine the relationship between migraine and a given disorder/trait, only some are discussed below. First, the causality between migraine and stroke has been investigated in three studies, two of which do not support a causal relationship between migraine and stroke (95–97), whereas one found a protective influence of large artery stroke (OR [95% CI] = 0.86 [0.76–0.96], P = 0.0067) on migraine, but no relation with stroke subtypes (97). Second, several other cardiovascular traits/risk factors and their possible causal relationship with migraine have been investigated, one showing that an increase in blood pressure directly contributes to migraine risk (84).…”
Section: Causality In Migrainementioning
confidence: 99%
“…As far as other diseases are concerned, there is no evidence of a causal association between depression and risk of IS [ 100 , 101 ], whereas one study has observed an association with increased risk of small vessel stroke (SVS) [ 100 ]. No causal associations were identified between migraine and AIS or stroke subtypes [ 102 ]. Impaired renal function is causally associated with an increased risk of LAS, but not other subtypes [ 110 ].…”
Section: Mendelian Randomization In Strokementioning
confidence: 99%